2021
DOI: 10.3389/fmicb.2020.622012
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functionality of HIV-1 Vif in APOBEC3 Counteraction and Cell Cycle Arrest

Abstract: Accessory proteins are a key feature that distinguishes primate immunodeficiency viruses such as human immunodeficiency virus type I (HIV-1) from other retroviruses. A prime example is the virion infectivity factor, Vif, which hijacks a cellular co-transcription factor (CBF-β) to recruit a ubiquitin ligase complex (CRL5) to bind and degrade antiviral APOBEC3 enzymes including APOBEC3D (A3D), APOBEC3F (A3F), APOBEC3G (A3G), and APOBEC3H (A3H). Although APOBEC3 antagonism is essential for viral pathogenesis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 139 publications
(115 reference statements)
0
21
0
Order By: Relevance
“…The HIV-1 protein Vif counteracts the antiviral activity of APOBEC3 enzymes. Vif binds to APOBEC3 enzymes and mediates their ubiquitination by the cellular Cullin5 E3-ubiquitin ligase, followed by their proteasomal degradation [ 4 , 21 , 22 , 23 , 24 ]. The counteraction ability of Vif depends on both the type of APOBEC3 enzymes and the variations within Vif.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV-1 protein Vif counteracts the antiviral activity of APOBEC3 enzymes. Vif binds to APOBEC3 enzymes and mediates their ubiquitination by the cellular Cullin5 E3-ubiquitin ligase, followed by their proteasomal degradation [ 4 , 21 , 22 , 23 , 24 ]. The counteraction ability of Vif depends on both the type of APOBEC3 enzymes and the variations within Vif.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic host defenses and anti-viral restriction factors limit replication and reverse transcription efficiency contributing to the generation of defective HIV genomes. APOBEC 3G, a cytosine deaminase, targets single-stranded DNA intermediates and promotes HIV-1 hypermutation by inducing guanine-to-adenine changes during the process of reverse transcription [59][60][61][62][63]. Sterile Alpha Motif-and HD-domain containing protein 1 (SAMHD1), a host viral restriction factor which reduces the concentration of intracellular nucleotides in resting CD4+ T cells and myeloid cells, limiting the efficiency and completion of reverse transcription [64][65][66][67].…”
Section: Generation Of Defective Hiv-1 Genomesmentioning
confidence: 99%
“…Although mostly known for its ability to target APOBEC3 restriction factors for proteasomal degradation ( Desimmie et al., 2014 ; Harris and Dudley, 2015 ), intense studies on the HIV-1 Vif accessory protein revealed that the cell cycle arrest induced by Vif occurs through its targeted degradation of B56 ( Greenwood et al., 2016 ; Marelli et al., 2020 ; Nagata et al., 2020 ; Salamango and Harris, 2020 ). Interestingly, although Vif does not encode an LxxIxE SLiM motif, co-expression of an LxxIxE-like peptide inhibitor known to outcompete B56 binders reduced degradation of B56 in a dose-dependent manner ( Salamango et al., 2020 ) suggesting that Vif recognition by B56 involves residues surrounding the LxxIxE SLiM binding pocket.…”
Section: Emerging Role Of Viral Pp2a Targeting Via Lxxixe Motif Mimicrymentioning
confidence: 99%